IMPLEMENTATION OF THE HAJJ PILGRIM PROTECTION POLICY WEST JAVA PROVINCE AT THE BEKASI HAJJ DORMITORY (STUDY ON THE IMPLEMENTATION OF THE HAJJ PILGRIMAGE IN 2023 - 2025) - Dwi Isti Anggraini; R. N. Afsdy Saksono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The weak enforcement of area order, the regulation of pilgrims entering/exiting the area, and the supervision of pilgrims' belongings, as mandated in Law Number 8 of 2019 concerning Hajj and Umrah Organization, indicates that the implementation of the Hajj pilgrim protection policy at the Bekasi Hajj Dormitory has not been optimal. This research aims to explore the factors contributing to the non-optimal implementation of the protection policy for Hajj pilgrims from West Java Province at the Bekasi Hajj Dormitory and to formulate strategies for optimizing the implementation of the Hajj Pilgrim protection policy for West Java Province at the Bekasi Hajj Dormitory. The research was conducted using a qualitative approach and a case study method on the Hajj implementation in 2023 – 2025 at the Bekasi Hajj Dormitory. Data collection was carried out through in-depth interviews with 12 key informants from the Bekasi Hajj Dormitory; Class I Health Quarantine Center Bandung; Bekasi City Resort Police; Bekasi City Ministry of Religious Affairs; Bekasi Hajj Dormitory Cooperative; Hajj Pilgrims from West Java Province for the years 2023 – 2025; and document review. The results show that the factors causing the non-optimal implementation of the Hajj pilgrim protection policy for West Java Province at the Bekasi Hajj Dormitory are: (1) availability of regulations, (2) availability of resources, (3) attitude of implementers, (4) policy communication, (5) implementation coordination, and (6) the attitude of the Hajj pilgrims. Five strategies were formulated to make the implementation of the Hajj pilgrim protection policy for West Java Province at the Bekasi Hajj Dormitory more optimal based on the analysis results: (1) establishing a Pos Silaturahim (Friendship Post), (2) regulating seasonal workers, (3) increasing the frequency of message delivery, (4) adding CCTV cameras, and (5) installing a CCTV monitor at the Security Post.